Productivity characteristics of pruned drip irrigated arabica coffee plants (Coffea arabica L., cv. Topázio MG -1190) - Rezende, Fátima Conceição; Oliveira, Sérgio dos Reis; Faria, Manoel Alves de; Arantes, Kelte Resende (Coffee Science - ISSN 1984-3909, 2007)
Irrigated coffee crop (Coffea arabica L.) studies are quite common but almost no information is available on pruned irrigated coffee crops. This work reports studies carried out in Lavras, Minas Geais, Brazil to evaluate the total yield, volumetric yield, beans ripening uniformity, beans size and defects on several irrigation laminas. Coffee plants (cv. Topázio MG-1190) eavely pruned after 65 months from planting date were irrigated using self compensating drippers placed 0.40 m from each other. Planting was done on a 1.8 x 0.7m spacing scheme under a split plot experimental design with four replicates, where four water lamina were compared in the plots and three N and K fertilization dates in the subplots. Irrigation took place on Tuesdays and Fridays and water lamina used was equivalent to 0% (L0 no irrigation), 40% (L1), 80% (L3), and 120% (L3) of the ballance between evaporation from a class A pan (ECa) and precipitation (ECa-P). Data from the 2002/2003 and 2003/2004 harvests, corresponding to all coffee beans picked from six plants from each replicate, were analyzed. Results indicate that irrigation increased productivity and volumetric yield of beans in both harvests but retarded beans ripening. Coffee quality was better in the first harvest than in the second.